Speech Therapy Practices for Children with Speech Delay: Exploring Techniques, Challenges, and Support Systems in Inclusive Preschool Education - Fitri , Nur Lailatul; Novitasari, Nurul; Habibah, Fita Hidayatul; Imamah, Zakiyatul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Delays in speech development in early childhood remain a prevalent developmental issue that impedes children’s ability to communicate and socialize effectively. This study investigates the implementation of speech therapy interventions for children with speech delay at the Smart Edu Tuban Inclusive Kindergarten (KB), focusing on the intervention process, supporting and inhibiting factors. Using a descriptive qualitative method with a single case study design, data were obtained through observation, interviews, and documentation involving key informants: the principal, a teacher-therapist, a parent, and a student with speech delay. The study reveals two main forms of intervention: (1) strengthening the speech organs through massage, brushing, and breath exercises, and (2) repetitive verbal training using visual aids. These methods are structured in four stages: initial assessment, planning, implementation, and evaluation. Supporting factors include complete therapeutic facilities, active parental involvement in reinforcing therapy at home, and the therapist’s competence. Inhibiting factors include children’s difficulty in articulating words and fluctuations in mood during therapy sessions. The findings highlight the importance of combining motoric stimulation and verbal repetition strategies within a structured and individualized therapy program. This case also underscores the critical role of environmental support, particularly from parents and educators, in enhancing therapeutic outcomes. The study contributes to understanding how inclusive early childhood institutions can develop adaptive therapeutic practices. However, as a single-case design, the findings cannot be generalized broadly. Further research with larger participant pools and experimental design is needed to assess the effectiveness of various intervention models and their applicability across diverse settings. Strengthening inter-institutional collaboration and integrating emotional support mechanisms are recommended to optimize therapy outcomes for children with speech delays.